2011
DOI: 10.1093/aobpla/plr002
|View full text |Cite
|
Sign up to set email alerts
|

Association of leaf micro-morphological characters with powdery mildew resistance in field-grown mulberry (Morus spp.) germplasm

Abstract: Background and aimsMicro-morphological characteristics can influence fungal infectivity. We sought links between micro-morphology and resistance to powdery mildew in mulberry with the intention of assisting selection of disease-resistant lines.MethodologyOver 3 years and under field conditions, we evaluated 30 lines of mulberry with contrasting susceptibilities to powdery mildew (15 resistant and 15 susceptible). Disease severity was related statistically to stomatal area, stomatal density, stomatal index, upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 58 publications
3
10
0
1
Order By: Relevance
“…The significant correlation of DSI with SF, TD, TSS and PP support the report of Chattopadhyay et al (2011) who reported strong negative association of powdery mildew resistance with SF and TD in mulberry. Similarly, a significant negative correlation of soluble sugar with black pod infection with cocoa (Nyadanu et al 2013) and phenol content with with soft rot infection of potato were also supported our findings.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The significant correlation of DSI with SF, TD, TSS and PP support the report of Chattopadhyay et al (2011) who reported strong negative association of powdery mildew resistance with SF and TD in mulberry. Similarly, a significant negative correlation of soluble sugar with black pod infection with cocoa (Nyadanu et al 2013) and phenol content with with soft rot infection of potato were also supported our findings.…”
Section: Discussionsupporting
confidence: 87%
“…The SF was determined as the number of stomata per unit leaf area (mm 2 ) (Xu & Zhou 2008). Trichome number was counted from five microscopic observations per entry along the mid-vein side using a Diaplan stereo-dissecting microscope and TD was estimated as the number of trichome per square millimetre (Chattopadhyay et al 2011).…”
Section: Assessment Of Morphological Featuresmentioning
confidence: 99%
“…The increased amount of BDM in O. basilicum as we reported is consistent with other reports of BDM incidence (Damicone, 2010;McGrath, 2011;Mersha et al, 2012;R€ omer et al, 2010;Wyenandt et al, 2010). Previous studies have demonstrated a correlation between high stomatal density and increased disease incidence with other pathogens on other crops (Alonso-Villaverde et al, 2011;Bala et al, 1992;Chattopadhyay et al, 2011;Furst, 1976;Gill and Nandpuri, 1978;Hern andez et al, 2006;Inder et al, 1999;Jhooty et al, 1978;Kramer and Boyer, 1995;Kumar et al, 2011;Mahajan and Gill, 1998;Mayee and Suryawanshi, 1995;Philip et al, 1991;Shaik, 1985;Sharma et al, 2001;Stenglein et al, 2005). This is the first report to show this same correlation with high stomatal density and increased BDM incidence and severity with Ocimum sp.…”
Section: Discussionsupporting
confidence: 91%
“…The correlation of stomata density to percentage of rust disease on soybean leaves at the 77 th DAP was highly strong with r value 0.9727. Additionally, Chattopadhyay et al (2011) found that the stomata and trichoma density of mulberry leaves had strong correlation to development of powdery mildew disease with r values 0.624 and -0.809, respectively. Pradana et al (2017) specified that the intensity of scab disease on sweet potato leaves at generative phase was extended to 85.10% due to the length of stomata on the upper leaves on susceptible cultivars, and 62.97% of intensity of the disease incidence was influenced by stomata density.…”
Section: Correlation Of Stomata Density Of Some Accessions Of Maize Gmentioning
confidence: 98%